PKCɛ switches Aurora B specificity to exit the abscission checkpoint - Tanya Pike (Nature Portfolio, 2016)
The Aurora B abscission checkpoint is activated when DNA is retained in the cleavage furrow on completion of anaphase. Here the authors show that PKCɛ directly phosphorylates Aurora B triggering a switch in Aurora B substrate specificity to elicit Borealin phosphorylation and abscission checkpoint exit.